Relationship Between Plasma Concentrations and Clinical Effects of Cariprazine in Patients With Schizophrenia or Bipolar Mania - Antonia Periclou; Susan Willavize; David Jaworowicz; Julie Passarell; Timothy Carrothers; Parviz Ghahramani; Suresh Durgam; Willie Earley; Margit Kapás; Tatiana Khariton (Wiley, 2020)
Population pharmacokinetic/pharmacodynamic modeling (via NONMEM) was used to describe longitudinal exposure‐response relationships for total cariprazine (sum of cariprazine and its major active metabolites) in 2,558 patients with schizophrenia or bipolar mania. Drug exposure metrics were explored for potential relationships with efficacy and safety end points. Total cariprazine exposures were significantly related to reductions in Positive and Negative Syndrome Scale (PANSS) or Young Mania Rating Scale (YMRS) total scores in schizophrenia or bipolar mania, respectively, via a maximum effect (Emax)‐type relationship. Typical steady‐state plasma concentrations after 3 and 4.5 mg/day were associated with 50% of maximum typical reductions in PANSS and YMRS total scores, respectively. Time‐weighted cariprazine exposures had significant relationships with the probability of common adverse events (AEs). Dose increase was associated with increased efficacy but was also associated with an increase in AEs. Results of these pharmacokinetic/pharmacodynamic analyses support that the recommended dose range (1.5-6 mg/day for schizophrenia and 3-6 mg/day for bipolar mania) provides an appropriate benefit‐risk balance between cariprazine efficacy and safety.